Floral Morphological Variation in Black Pepper (Piper nigrum L.) Varieties and Hybrid Lines - Wahyuni, Sri; Susilowati, Mariana; Sirait, Nursalam; Bermawie, Nurliani (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
The inter-variety crossing is a promising approach to increase black pepper production. However, successful hybridization hinges on floral characteristics. This study investigated the floral morphology of diverse pepper varieties and their hybrid offspring. Eighteen genotypes, including parent varieties and F1 hybrids, were cultivated in pots under greenhouse conditions at the Indonesian Spice and Medicinal Crops Research Institute, Bogor. Flower and fruit traits were observed. Results indicated variability in spike morphology. While most ripe spikes were yellowish-green, exceptions included LH 20-1 and LH 22-1. Ciinten and LH 4-5 displayed superior spike length and fruit set, contrasting with the shorter, less productive spikes of 20-1, 22-1, and 455-N2-97. Stigma receptivity and another dehiscence coincided in Ciinten, N2BK, LH 6-2, and LH 4-5, simplifying the hybridization process. Conversely, earlier stigma receptivity in Petaling 1, Petaling 2, Natar 1, Natar 2, LH 44-9, LH 20-1, and LH 22-1 facilitated castration procedures. These findings offer valuable insights for optimizing pepper breeding programs.